1972
DOI: 10.1530/jrf.0.0300433
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophic Activities of Anterior Pituitary and of Blood Plasma and Ovarian Response to Exogenous Gonadotrophin in Moulting Hens

Abstract: The total gonadotrophic activities of the anterior pituitary glands and blood plasma of hens, Gallus domesticus, during the moulting period were estimated using the assay method based on the weight increase of chick testis. The activities in both the pituitary and the blood of hens in the four groups classified according to the progress of moult were significantly higher than those of laying hens. Nevertheless, no detectable level of serum vitellin and a completely regressed ovary were found in moulting hens.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The total gonadotropin content of the latter in serum (Bailey et al, 1952) as well as in the anterior pituitary (Nakajo et al, 1961) proves to be higher than in the laying hen. Imai et al (1972) found that this high gonadotropin content in the non-laying hen can be attributed to an increase of FSH rather than of LH. Consequently, the suggestion seems to be justified that in maturing and adult hens injected with 5-methoxytryptophol, the weight of the gonadal system (ovaries and follicles) is decreased while the FSH content increases.…”
Section: Resultsmentioning
confidence: 87%
“…The total gonadotropin content of the latter in serum (Bailey et al, 1952) as well as in the anterior pituitary (Nakajo et al, 1961) proves to be higher than in the laying hen. Imai et al (1972) found that this high gonadotropin content in the non-laying hen can be attributed to an increase of FSH rather than of LH. Consequently, the suggestion seems to be justified that in maturing and adult hens injected with 5-methoxytryptophol, the weight of the gonadal system (ovaries and follicles) is decreased while the FSH content increases.…”
Section: Resultsmentioning
confidence: 87%
“…An increase in ovarian and oviductal mass in response to PMSG was reported in most previous studies (Zadworny and Etches 1988;Petitte and Etches 1989;Wakabayashi et al 1996). In several studies, growth of yellow follicles was observed (Imai et al 1972;Zadworny and Etches 1988;Wakabayashi et al 1996), but these follicles were not arranged in an ovarian hierarchy. Only one study has reported a normal ovarian hierarchy in some individuals following PMSG treatment (Petitte and Etches 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have used either daily injections (e.g. Imai et al 1972;Johnson et al 1985;Petitte and Etches 1989) or the implantation of an osmotic pump (Wakabayashi et al 1992(Wakabayashi et al , 1996 to deliver hormone. Both methods have their advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The laying pullets of one group were fed Methallibure (ICI compound 33828) at a concentration of 0-02% in the normal dry-mash ration based on the results of preliminary experiments using 0-01% and 0-02% concentrations (Sykes, 1964 Serum vitellin levels were measured by the immunological procedure described previously (Imai, Tanaka & Nakajo, 1972 Kiyoshi Imai carboxymethyl (CM)-or diethylaminoethyl(DEAE)-cellulose was used for a further purification. The GP-extract obtained from each batch of CAP was dissolved in 5 ml 4 mM-ammonium acetate at pH 5-5.…”
Section: Experimental Hensmentioning
confidence: 99%